(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
Outbreaks of methanol poisoning occur frequently on a global basis, affecting poor and vulnerable populations. Knowledge regarding methanol is limited, likely many cases and even outbreaks go unnoticed, with patients dying unnecessarily. An autopsy based study done at new civil hospital, Surat where suspected cases of methanol poisoning were admitted to hospital for treatment and some were brought dead. Total 17 cases (15 male and 2 female) were subjected to post mortem examination in which viscera were preserved for histopathological and chemical analysis report. Additionally urine and blood also were taken for qualitative and quantitative estimation of methyl alcohol. The cause of death given in 4 cases was methanol poisoning and 12 cases were methanol poisoning and its complications while in 1 case it waspulmonary oedema associated with interstitial lung disease.